2016
DOI: 10.1016/j.jid.2016.06.625
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Dictate the Apoptotic Response of Melanoma Cells to TH588

Abstract: The effect of MTH1 inhibition on cancer cell survival has been elusive. Here we report that although silencing of MTH1 does not affect survival of melanoma cells, TH588, one of the first-in-class MTH1 inhibitors, kills melanoma cells through apoptosis independently of its inhibitory effect on MTH1. Induction of apoptosis by TH588 was not alleviated by MTH1 overexpression or introduction of the bacterial homolog of MTH1 that has 8-oxodGTPase activity but cannot be inhibited by TH588, indicating that MTH1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
11
34
0
Order By: Relevance
“…We thus suggest that the improved survival in response to TH588 and TH1579 treatment in cells, where the spindle assembly checkpoint is disturbed, can be explained by less time spent in mitosis, ultimately resulting in lower levels of ROS generation and reduced accumulation of toxic 8-oxodG in DNA. Previously, both we and others have demonstrated that cell death caused by TH588 treatment is associated with ROS formation, supporting this hypothesis[25,26]. Hence, MTH1i of 8-oxodGTPase only becomes relevant in presence of ROS in mitotically arrested cells.…”
supporting
confidence: 76%
“…We thus suggest that the improved survival in response to TH588 and TH1579 treatment in cells, where the spindle assembly checkpoint is disturbed, can be explained by less time spent in mitosis, ultimately resulting in lower levels of ROS generation and reduced accumulation of toxic 8-oxodG in DNA. Previously, both we and others have demonstrated that cell death caused by TH588 treatment is associated with ROS formation, supporting this hypothesis[25,26]. Hence, MTH1i of 8-oxodGTPase only becomes relevant in presence of ROS in mitotically arrested cells.…”
supporting
confidence: 76%
“…Similar effects of TH588 regarding cellular survival were shown recently [15, 25, 28]. Our results show a potent induction of apoptotic cell death mechanisms upon TH588 treatment (Fig 2).…”
Section: Discussionsupporting
confidence: 91%
“…Our results show a potent induction of apoptotic cell death mechanisms upon TH588 treatment (Fig 2). An increase of apoptosis due to TH588 treatment has also been described lately [15, 25]. The PI3K-Akt-mTOR pathway is one of the principal proliferative pathways and often up-regulated in human cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…While MTH1 function may be critical to survival in cells with elevated levels of ROS, MTH1 is dispensable in cancer cells under normal culture conditions. Wang et al (26) reported that the sensitivity of melanoma cells to TH588 is correlated with the level of endogenous ROS, although the cytotoxicity of TH588 is not associated with its inhibitory effect on MTH1. In the present study, TH588 enhanced the formation of 8-oxo-dG induced by PEITC (Fig.…”
Section: Discussionmentioning
confidence: 99%